Fundamentos economicos de la sociedad del conocimiento. (Economic Foundations of the Knowledge Society. With English summary.) - David, P; Foray, D (2002)
The knowledge society is a feasibility that, should it come true, will turn the forms of coexistence and production upside down. The authors examine one of its main pillars, the knowledge-based communities, and the challenges to be overcome in order to make the former happen.